2010
DOI: 10.1161/circep.110.936161
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparison of Cardiac Imaging Using Intracardiac Echocardiography With Transesophageal Echocardiography in Patients With Atrial Fibrillation

Abstract: Background-The Intracardiac Echocardiography Guided Cardioversion Helps Interventional Procedures study evaluatedthe concordance of intracardiac echocardiography (ICE) with transesophageal echocardiography (TEE) in patients with atrial fibrillation (AF). Methods and Results-Patients with AF undergoing right heart catheterization underwent left atrium (LA) and interatrial septal (IAS) imaging by TEE and ICE. A blinded comparison of the 2 modalities was performed at a core laboratory. Ninety-five patients aged 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 20 publications
2
34
1
4
Order By: Relevance
“…Patients in whom discontinuation of systemic anticoagulation is being considered should consider undergoing continuous ECG monitoring to screen for asymptomatic AF/AFL/AT. [406,407], other studies have reported that CT scanning can identify left atrial appendage thrombi with good sensitivity but moderate specificity [408]. Consistent with these findings, the members of this task force do not recommend that ICE or CT imaging be used to screen for LA thrombi in patients who are at high risk of stroke, and TEE is warranted.…”
Section: Post-ablationmentioning
confidence: 83%
See 1 more Smart Citation
“…Patients in whom discontinuation of systemic anticoagulation is being considered should consider undergoing continuous ECG monitoring to screen for asymptomatic AF/AFL/AT. [406,407], other studies have reported that CT scanning can identify left atrial appendage thrombi with good sensitivity but moderate specificity [408]. Consistent with these findings, the members of this task force do not recommend that ICE or CT imaging be used to screen for LA thrombi in patients who are at high risk of stroke, and TEE is warranted.…”
Section: Post-ablationmentioning
confidence: 83%
“…The heparin dose should be adjusted to maintain an ACT of at least 300-350 s throughout the procedure. Approximately one third of the task force uses a target ACT of 350 s, especially in patients with spontaneous echo contrast or significant atrial enlargement [402,407,411].…”
Section: Intraprocedural Anticoagulationmentioning
confidence: 99%
“…One alternative to TEE is the use of intracardiac echocardiography (ICE), which has proven to be useful in a variety of interventional procedures. 8 The majority of data on the safety of percutaneous LAA closure comes from selected centers and operators with considerable expertise in the procedure. Outcomes attained in the context of clinical trials might not be reproducible in real-world clinical practice.…”
mentioning
confidence: 99%
“…ICE can provide multiple views and detailed LAA imaging which facilitates detection of potential thrombi [39,40]. Although ICE is less sensitive than TEE for thrombus detection [41], it can serve as a complementary method, especially when equivocal TEE findings merit further evaluation. However, because ICE is an invasive procedure, it is not typically used in daily practice and is mainly reserved for planned interventional cardiac procedures in a catheterization laboratory setting.…”
Section: Cviamentioning
confidence: 99%